Feline lymphoma: a pilot study of prevalence and course features - Suprunenko, О. О.; Супруненко, О. О.; Beliy, Dmitry Dmitrievich; Beliy, Dmitry; Beliy, D. D.; Bely, Dmitry Dmitrievich; Bely, Dmitry; Bely, D. D.; Bilyi, D. D.; Bilyi, D.; Belyi, D. D.; Bilyi, Dmytro; et al. (Дніпровський ДАЕУ, 2023)
The results of the analysis of the medical histories of 36 cats with lymphoma, a malignant tumor disease of the lymphatic system, are presented. The relevance of the problem is due to the high level of morbidity and mortality, as well as the complexity of lymphoma verification. The multi-vector nature of damage to body systems and tissues due to lymphomas required the use of a wide range of diagnostic measures. The distribution of lymphoma in cats in the conditions of veterinary medicine hospitals of the cities of Dnipro and Zaporizhzhia was studied taking into the account age and breed susceptibility. The structure of feline lymphoma diseases based on its anatomical forms has been established. Changes in general clinical and biochemical blood markers in cats with lymphoma were determined. It was established that in the structure of the incidence of lymphoma in cats, a significant share is occupied by half-breeds (36.1 %) and representatives of Scottish (22.2 %) and British (19.4 %) breeds, aged 8–10 years (36.1 %) and older (33.3 %). It has been shown that the probability of lymphoma in cats increases progressively with age. In the vast majority of cases, alimentary (41.6%) and multicentric (30.6%) forms of lymphoma were verified against the background of a high risk of damage to any tissue or organ. Clinical signs are correlated with anatomical forms of lymphoma, but in the presence of individual features of the disease progression. Lymphoma progress is asymptomatic during the first stage. The analysis of hematological and biochemical markers of the blood of cats with lymphoma confirmed the inhibition of hematopoietic mechanisms and immune protection against the background of signs of intoxication of the body. The degree of violation of biological mechanisms depends on the affected tissues / body systems and accompanying diseases of viral (leukemia, immunodeficiency of cats) and noninfectious (chronic renal failure, enteropathy) etiology. The obtained results confirmed that further research is required to clarify the role of etiological factors (primarily, the external environment), a better understanding the biological mechanisms of initiation and progression of the disease as well as promising therapeutic targets for the treatment of lymphoma in cats. Представлено результати аналізу історій хвороби 36 котів, хворих на лімфому – злоякісне пухлинне захворювання лімфатичної системи. Актуальність проблеми обумовлена високим рівнем захворюваності та летальності, а також складністю верифікації лімфоми. Багатовекторність ураження систем і тканин організму за лімфоми вимагав використання широкого спектру діагностичних заходів. Вивчено поширення лімфоми у котів в умовах лікарень ветеринарної медицини міста Дніпро та Запоріжжя із урахуванням вікової і породної сприйнятливості. Встановлено структуру захворювань котів на лімфому за її анатомічними формами. Визначено зміни загальноклінічних і біохімічних маркерів крові у котів із лімфомою. Встановлено, що в структурі захворюваності котів на лімфому значну частку займають метиси (36.1 %) та представники шотландської (22.2 %) і британської (19.4 %) порід, віком 8–10 років (36.1 %) та старших (33.3 %). Показано, що ймовірність захворювання котів на лімфому прогресивно збільшується із віком. У переважній більшості випадків верифіковано аліментарну (41.6 %) та мультицентричну (30.6 %) форму лімфоми на фоні високого ризику ураження будь-якої тканини або органу. Із анатомічними формами лімфоми корелюють клінічні ознаки, але за наявності індивідуальних особливостей перебігу захворювання. На перших стадіях лімфома перебігає безсимптомно. Аналіз гематологічних та біохімічних показників крові котів із лімфомою засвідчив пригнічення механізмів кровотворення та імунного захисту на фоні ознак інтоксикації організму. Ступінь порушення біологічних механізмів залежить від уражених тканин / систем організму та супутніх захворювань вірусної (лейкемія, імунодефіцит котів) та незаразної (хронічна ниркова недостатність, ентеропатія) етіології. Отримані результати засвідчили необхідність подальших досліджень етіологічних чинників (насамперед, зовнішнього середовища), більш детального вивчення біологічних механізмів ініціації і прогресування захворювання, а також перспективних терапевтичних мішеней для лікування лімфоми у котів.
Лімфома котів: пілотне дослідження поширення та особливостей перебігу
Білий Дмитро Дмитрович https://orcid.org/0000-0003-3896-0384
Keywords: biochemical blood changes; біохімічні зміни крові; cats; коти; tumor; пухлини; lymphoma; лімфома; distribution monitoring; моніторинг поширення; breed and age susceptibility; породна і вікова сприйнятливість; hematological disorders; гематологічні порушення